UPAYA MENINGKATKAN MINAT BELAJAR SISWA MELALUI PENDEKATAN COLLABORATIVE PROBLEM - Samosir, Benny Sofyan; Lubis, Julvian Setiawan (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2019)
AbstractThis research was conductedwith background of students' low interest in learning mathematicsat the SMK Muhammadiyah 13 Sibolga. In order to overcome this problem, researcher appliedthe Collaborative Problem Solving learning approach. Which method was expected to be ableto increase the learning interest of Class X Office Administration students, besides that thepurpose of this research to increase student activity, then this approach was expected to improveteacher teaching skills through the Collaborative Problem Solving learning approach in class XOffice Administration. The type of this research was Classroom Action Research. This researchwas focused on students of Class X Office Administration SMK Muhammadiyah 13 Sibolgawith the number of respondents 39 people. While the techniques and tools of data collectionwere questionnaires and observations. The results of this study showed the learning interest ofstudents in the first cycle with an average value of 25.33 or a percentage of 50.67% in thesecond cycle to 34.3 or the percentage of 68.7% with an increase of 18.03%. The level ofactivity of students towards mathematics increased, this was obtained from the percentage of60.1% in the first cycle, and 88.2% in the second cycle increased by 28.1%. The ability ofteachers to manage learning percentage was 72% in the first cycle and 96% in the second cycle,with an increase of 24%.Keywords: Learning Approach, Collaborative Problem Solving, Trigonometry.